2010
DOI: 10.1111/j.1740-0929.2010.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating and rumination behaviour in Brahman grade cattle and crossbred water buffalo fed on high roughage diet

Abstract: The purpose of this study is to compare feeding and other behavior and nutrient digestibility of tropical grade Brahman (body weight (BW) = 231 kg ± 12.4; n = 3) and crossbred water buffalo (BW = 300 kg ± 13.9; n = 3). This experiment on digestibility and measures of muscles of mastication utilized one-way, and animal behavior two-way, analysis of variance, respectively. Two video camcorders were installed in each pair of buffalo and Brahman for 24 h period programmed on the 107th, 109th and 111th days of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Studies have shown that buffaloes are more tolerant of roughage compared with cattle, and the buffalo feces recovery of acid detergent lignin (ADL) is 88.90% which is lower than that of chromic oxide (Cr 2 O 3 ) (95.89%) and acid‐insoluble ash (97.14%) in roughage digestibility experiments using indicator methods [16]. These results may be related to the lignin‐degrading bacteria of buffalo rumen [17]. Although lignin transformation is well‐documented, few studies on lignin degradation by rumen microorganisms [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that buffaloes are more tolerant of roughage compared with cattle, and the buffalo feces recovery of acid detergent lignin (ADL) is 88.90% which is lower than that of chromic oxide (Cr 2 O 3 ) (95.89%) and acid‐insoluble ash (97.14%) in roughage digestibility experiments using indicator methods [16]. These results may be related to the lignin‐degrading bacteria of buffalo rumen [17]. Although lignin transformation is well‐documented, few studies on lignin degradation by rumen microorganisms [18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, observations of crossbred water buffaloes raised under feedlot conditions reveal that the duration of standing behaviour was significantly shorter (659 vs. 857 min; P ≤ 0.001), while the lying posture was longer (643 vs. 578; P ≤ 0.10) than in tropical grade Brahmans (Vega et al 2010). The same authors utilised two video camcorders installed in corrals with Brahmans and crossbred water buffaloes in an attempt to determine their respective frequencies of food intake, performance, and nutrient digestibility.…”
Section: Trophic Behaviourmentioning
confidence: 72%
“…This efficiency in transforming pasture may be due to this species' slow, efficacious chewing motion that involves more developed muscle fibres for rumination than in the case of cattle, including the digastric muscle, the masseter muscle, the pterygoid muscle, and even the tongue (P ≤ 0.05) (Vega et al 2010). Other important features include its larger corporal volume, slower movement, smaller outflow rate, and higher bacterial activity (Napolitano et al 2013).…”
Section: Characteristics Of the Water Buffalomentioning
confidence: 99%
See 1 more Smart Citation
“…These factors result in a slower transition of both solids and liquids [63]. In addition, Vega et al [64] reported that the number of buffalo mastication movements is lower than in cattle because of the wider diameter of pterygoid and masseter muscles and tongue, thus suggesting a greater chewing strength and a more efficient ruminating process.…”
Section: Meat Productionmentioning
confidence: 99%